Ergonomic Risk of Musculoskeletal Disorders in Laundry Workers of Public Hospital in Kupang City - Reno Raines Saingo; Luh Putu Ruliati; Afrona E. L. Takaeb (Media Kesehatan Masyarakat, 2022)
Musculoskeletal disorders (MSDs) are health problems often experienced by workers due to several reasons, namely age, gender, body mass index, length of work, workload, work attitude and temperature. Hospital laundry workers are nonmedical staff in charge of washing dirty linens. As they use physical abilities, the workers have a high risk of musculoskeletal complaints. This study aimed to determine and analyze the risk of ergonomic MSDs in laundry workers at three public hospitals. This study was an analytic survey with a cross-sectional design. The study was located at hospital Prof. Dr. W. Z. Johannes, RST Wirasakti and RSB Titus Uly Kupang, and was conducted in January - August 2021. The population in this study was all laundry staff who worked in three hospitals. The sample of 33 people was taken using total sampling technique. The results showed that there was a relationship between age (p= 0.027), years of service (p= 0.001), workload (p= 0.002), work attitude (p= 0.001) and temperature (p= 0.001) with MSDs. Gender (p= 0.183) and body mass index (p= 0.282) were found unrelated to MSDs. The Hospital Occupational Health and Safety (K3) Management needs to be improved by providing occupational health promotion, ergonomic work attitude training for laundry workers and provision of adequate laundry facilities to minimize the occurrence of MSDs.